Inquiry-based learning put to test: Long-term effects of the Swedish science and technology for children program - Erik Mellander; Joakim Svärdh (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
We quantitatively evaluate the effects in grade 9 on content and process skills in sciences, from participation in the Swedish science and technology for children program, the NTA program. Students predominantly participate in this program during grades 1-6. Our outcome measures are scores and grades on nationwide tests, and course grades, in biology, chemistry and physics, 2009-2010. A nationally representative random sample of almost 16 000 test-taking students is coupled with multi-level information about the NTA, and background factors. Non-random selection into the program is addressed by propensity score analysis. The matched sample of pairs of NTA participants and non-participants, determined by the propensity scores, is quite well behaved, although there are significant, but small, differences for some of the matching covariates. We find significantly positive effects on test scores (average increase 16.4%) and test grades in physics, but not in biology and chemistry. No significant effects are found for course grades.
Keywords: 330; quantitative evaluation; national standardized tests; representative sample; non-random selection; propensity score analysis; multi-level modeling; post-matching multivariate regression